Exacerbation of ichthyosis vulgaris phenotype by co-inheritance of STS and FLG mutations in a Chinese family with ichthyosis: a case report - Xiong Wang; Lu Tan; Na Shen; Yanjun Lu; Ying Zhang (BMC, 2018)
Abstract Background X-linked ichthyosis (XLI) is a recessive keratinization condition caused by deficient activity of steroid-sulfatase due to mutations in steroid sulfatase (STS) gene located on the X chromosome. In contrast, ichthyosis vulgaris (IV) is caused by filaggrin deficiency due to semi-dominant loss-of-function mutations of filaggrin (FLG) gene. Filaggrin defects could synergize with XLI to exacerbate its phenotype. Case presentation We report a Chinese family with patients presenting diverse phenotype of Keratosis pilaris. A next-generation sequencing panel interrogating 25 ichthyosis related genes with sequencing coverage of the coding regions and splice site junctions, was applied to screen genetic mutations. A gross deletion encompassing the STS gene ranging from exon 1-10 and the FLG c.3321delA mutation were identified in a 31-year old male proband, one of his sister, and his mother, and all the three patients showed obvious symptom. The deletion of STS gene was confirmed by real-time quantitative PCR. The proband's another sister and his two nephews carried only FLG c.3321delA mutation. Patients carried both mutations presented more severe symptom, while those only carried FLG c.3321delA mutation showed slight or normal phenotype. Conclusions In conclusion, we found that the IV phenotype was exacerbated by co-inheritance of STS and FLG mutations in a Chinese family with ichthyosis. Other genomic regions no included in the study might be also involved in phenotypic modifications.